Le Giornate Mondiali della Gioventù – i giovani e il beato Giovanni Paolo II - Andrzej Kiciński (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II, 2012)
Many people say that World Youth Day is Pope John Paul II’s best invention. However, he used to say that it was the young people themselves who invented it. The Pope felt that the Church’s concern for the younger generations should be made known. He issued invitation to young people to come to Rome for Palm Sunday. After two gatherings, at the end of 1985 he announced the institution of the World Youth Day that was to be celebrated every year in the dioceses. The diocesan celebrations were soon joined by international gatherings. The author of this article presents World Youth Day as the Church’s Day for youth and with youth. This idea is not an alternative to ordinary youth ministry, often carried out with great sacrifice and self-denial. Indeed it intends actually to consolidate this work by offering new encouragement for commitment, objectives which foster ever greater involvement and participation. By aiming to foster greater fervour in apostolate among young people, the Church desires to make them the protagonists of an apostolate which will spread to the other ages and situations of life in the ambit of new evangelization.